Trade-off between pollinator-wildflower diversity & grassland yields - Nicholas J. Balfour; Ciaran Harris; Jonathan Storkey; Francis L. W. Ratnieks (npj Biodiversity)
Abstract This is a critical moment for land use policy globally, with many countries (e.g. the UK and the European Union) currently undertaking significant green reforms of their agricultural policies. Despite their importance for maintaining agricultural outputs and plant diversity, the effects of artificial soil enrichment on pollinators remain poorly understood. Our two-year study at the world’s longest-running ecological experiment, Park Grass, Rothamsted, examines the relationship between soil fertilisation, grassland yield and biodiversity. Our data show a large and significant negative effect of the major plant nutrients (NPK) on the abundance, species richness and functional diversity of both pollinators and flowering plants. The results also indicate a large and significant trade-off between productivity and biodiversity. Our findings are a salutary reminder of the challenge in reconciling conflicting aims in farmland management and strongly suggest that financial incentives are necessary to offset yield reductions to improve biodiversity outcomes in agricultural grasslands.